2020
DOI: 10.7759/cureus.10294
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in an Intrauterine Growth Restriction (IUGR) Infant with Congenital Heart Disease: Case Report and Literature Review

Abstract: In pediatrics, reported coronavirus disease-19 (COVID-19) cases showed that this category of patients usually presented with no symptoms or mild to moderate COVID-19 disease. However, infants less than one-year-old had a more severe presentation or even critical condition and respiratory failure. Patients with chronic disease and congenital heart disease (CHD) may have serious effects on course of COVID-19 in neonate and early infancy. There is very limited data about confirmed COVID-19 cases with CHD in neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Nevertheless, although the molecular evolution and mutation rate of SARS-CoV-2 seems to be less than for influenza or SARS-CoV-1, special attention is needed as in other emergent diseases such as Zika Virus, a single mutation was enough to increase the Zika Virus neurotropism and increase the incidence of microcephaly in the Brazil outbreaks in 2015 [200,201]. Though there is no evidence to support frequent vertical transmission and teratogenic effects in the unborn child from infected patients, due to the increased risk of respiratory viral infections during pregnancy [202,203], the continuous molecular evolution of variants of SARS-CoV-2 [204], and the adverse outcomes of pregnancy such as preterm birth, preeclampsia, intrauterine growth restriction [205][206][207], there is a consensus in the scientific community that SARS-CoV-2 infection during pregnancy is worthy of special attention and further studies [208][209][210].…”
Section: Effects Of Sars-cov-2 In Human Reproduction After Conception...mentioning
confidence: 99%
“…Nevertheless, although the molecular evolution and mutation rate of SARS-CoV-2 seems to be less than for influenza or SARS-CoV-1, special attention is needed as in other emergent diseases such as Zika Virus, a single mutation was enough to increase the Zika Virus neurotropism and increase the incidence of microcephaly in the Brazil outbreaks in 2015 [200,201]. Though there is no evidence to support frequent vertical transmission and teratogenic effects in the unborn child from infected patients, due to the increased risk of respiratory viral infections during pregnancy [202,203], the continuous molecular evolution of variants of SARS-CoV-2 [204], and the adverse outcomes of pregnancy such as preterm birth, preeclampsia, intrauterine growth restriction [205][206][207], there is a consensus in the scientific community that SARS-CoV-2 infection during pregnancy is worthy of special attention and further studies [208][209][210].…”
Section: Effects Of Sars-cov-2 In Human Reproduction After Conception...mentioning
confidence: 99%
“…At the last follow up point, three patients were discharged and one was still hospitalized. [30][31][32][33] Bezerra et al reported that one female patient was diagnosed with COVID-19 infection after a Fontan procedure for hypoplastic left heart syndrome. Despite the patient was admitted to the ICU and experiencing multiple pulmonary combined with other complications, she was fully recovered and discharged.…”
Section: Overview Of Case Reports In the Literaturementioning
confidence: 99%
“…Specifically, 7 million cardiovascular (CV)‐related deaths in adulthood occur each year due to growth restriction in early life (Baum et al., 2003 ). The COVID‐19 pandemic has reduced food availability, and worsened dietary practices, which likely increases the prevalence of postnatal growth restriction (PGR) (Elbehery et al., 2020 ; Jafri et al., 2021 ). Therefore, the health outcomes of growth restriction are relevant to the current CV health crisis facing the world today.…”
Section: Introductionmentioning
confidence: 99%